Chinese philosophy Chinese political philosophy, metaphysics, epistemology and comparative philosophy - Wen Haiming (Cultural China series, 2017)
This book aims to explore Chinese philosophical characteristics of different philosophers in various periods, and distinguish "Chinese philosophical sensibility" motivating their thoughts. In doing so, the author employs Western philosophical categories to describe different issues in the history of philosophy : Chinese political philosophy in pre-Qin era, Chinese metaphysics from Han to Tang dynasties, Chinese epistemology from Song to Ming dynasties, and modern Chinese-Western comparative philosophy. The author provides readers with a clear conception of Chinese philosophical sensibility and its evolution throughout history.